2021
DOI: 10.3389/fnagi.2021.707732
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Post-stroke Epilepsy Following Stroke-Associated Acute Symptomatic Seizures

Abstract: Objective: Post-stroke epilepsy (PSE) is associated with increased morbidity and mortality. Stroke-associated acute symptomatic seizures are an important risk factor: 20.8–34.3% of these patients will go on to develop PSE. Identifying these “high risk” individuals may result in earlier PSE diagnosis, treatment, and avoidance of seizure-related morbidity. This study was to identify predictors of PSE development in patients with stroke-associated acute symptomatic seizures.Participants and Methods: This was a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
0
17
0
2
Order By: Relevance
“…In our Cox regression model, moderate NIHSS scores ( 5 9 ) and severe NIHSS scores (≥10) were associated with 1.4-fold and 1.98-fold increases in the risk of PSE, respectively. In previous studies, a high NIHSS score at the time of stroke admission was consistently found to be a risk factor for PSE ( 9 , 15 , 17 ). In our study, the frequency of stroke recurrence was 18.9% during 16-year follow-up, similar to that in previous studies (6%−19%) ( 37 39 ), and stroke recurrence was independently associated with the development of PSE.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In our Cox regression model, moderate NIHSS scores ( 5 9 ) and severe NIHSS scores (≥10) were associated with 1.4-fold and 1.98-fold increases in the risk of PSE, respectively. In previous studies, a high NIHSS score at the time of stroke admission was consistently found to be a risk factor for PSE ( 9 , 15 , 17 ). In our study, the frequency of stroke recurrence was 18.9% during 16-year follow-up, similar to that in previous studies (6%−19%) ( 37 39 ), and stroke recurrence was independently associated with the development of PSE.…”
Section: Discussionmentioning
confidence: 82%
“…Because of distinct characteristics and mechanisms of seizure, most studies set a 7-day interval to categorize early- and late-onset poststroke seizures ( 9 , 11 , 17 , 19 , 27 ). However, this study was unable to identify the exact timing of the first seizure after stroke onset due to the limitation of using the Taiwan NHI research database.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the definition for acute symptomatic seizures of the International League Against Epilepsy (ILAE), seizures after ICH were classified as early seizures (seizures that occurred within 7 days post-stroke) or late seizures (spontaneous unprovoked seizures that occurred beyond 7 days post-stroke) ( 21 ). Early seizures were extracted from inpatient medical records, while late seizures were identified by medical records and tele-interview based on a standardized questionnaire for screening late seizures ( Supplementary Table S1 ) ( 22 ). The follow- up was conducted by a telephone interview and ended at death or in January 2020 (TJH) and October 2021 (WZH).…”
Section: Methodsmentioning
confidence: 99%